Memonics efficiency in language practice - Falkovskaya, Anastasia V. (2018)
The study of languages requires high intellectual effort, as well as emotional and mental stress. Taking into account the interdependence of mental and communicative processes with human cognitive activity, one should recognize the productivity of mnemotechnical technique application in language learning practice. In this regard, the object of our attention are mnemonics, which, based on the positive resources of native speaker development, contribute to the painless memorization and further use of difficult material. The urgency of the article is connected with the understanding of mnemotechnical technique importance in the process of language mastering. In this article, mnemotechnical techniques are described, used for Russian and German language mastering. They substantiate the expediency and the effectiveness of their application during the study of native and foreign languages. The classification of mnemonic techniques by classes (I. Thompson) and basic methods (R.L. Oxford) is of particular interest. The purpose of mnemotechnical method study is to improve the methodology of language teaching. Based on the analysis of the described mnemotechnical methods, they provided the rationale for their application in the wide practice of native and foreign language teaching. The practical significance is represented by the identification of mnemonic specific features, forms and methods in linguistic training.